Effectiveness of scoliosis-specific exercises for adolescent idiopathic scoliosis compared with other non-surgical interventions: a systematic review and meta-analysis. Issue 2 (June 2019) - Thompson, J.Y.; Williamson, E.M.; Williams, M.A.; Heine, P.J.; Lamb, S.E.; ,
Abstract: Study design: Systematic review and meta-analysis. Objective: To assess the effectiveness of scoliosis-specific exercises (SSE) on adolescent idiopathic scoliosis (AIS) compared with other non-surgical interventions. Background: AIS is a complex deformity of the spine that develops between the age of 10 years and skeletal maturity. SSE are prescribed to patients to reduce or slow curve progression, although their effectiveness is unknown. Methods: Electronic databases were searched for relevant studies. Randomised controlled trials were eligible if they compared SSE with non-surgical interventions for individuals with AIS. Three authors independently extracted data, evaluated methodological quality and assessed the quality of evidence. Meta-analysis was performed where possible; otherwise, descriptive syntheses are reported. Results: Nine randomised controlled trials were included. Four had a high risk of bias, three had an unclear risk and two had a low risk. Very-low-quality evidence indicated that SSE improved some measures of spinal deformity, function, pain and overall health-related quality of life (HRQoL). Very-low-quality evidence suggested that SSE had no effect on self-image and mental health. Very-low-quality evidence showed that bracing was more effective than SSE on measures of spinal deformity. However, SSE showed greater improvements in function, HRQoL, self-image, mental health and patient satisfaction with treatment. No differences were found for pain or trunk rotation. Conclusions: SSE may be effective for improving measures of spinal deformity for people with AIS, but the evidence is of very low quality. Future studies should evaluate relevant clinical measures and cost-effectiveness using rigorous methods and reporting standards.